2016
DOI: 10.1109/mits.2016.2533979
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Intelligent Speed Adaptation for Long-Distance Informal Public Transport In South Africa

Abstract: Abstract-Informal transport refers to the collective passenger road transport industry with little or no regulatory control of its operations, usually characterised by unplanned and ad-hoc service delivery. The notoriously dangerous informal transport industry in South Africa -dominated by minibus taxis -has been shown to disregard the posted speed limit on long-distance trips. Not only do they frequently exceed the differentiated speed limit imposed on minibus taxis, but also the speed limit imposed on normal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In most cases where driver engagement was required, such as in works that sought to reduce speeding [47], monitor driving behaviours [27,51] or detect drowsiness [61], smart phones (specifically Android) were used. Due to their ubiquity, smart phones have also been used as cost-effective ways of collecting data about road conditions for infrastructure planning [39,53,57].…”
Section: Cross-cutting Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases where driver engagement was required, such as in works that sought to reduce speeding [47], monitor driving behaviours [27,51] or detect drowsiness [61], smart phones (specifically Android) were used. Due to their ubiquity, smart phones have also been used as cost-effective ways of collecting data about road conditions for infrastructure planning [39,53,57].…”
Section: Cross-cutting Connectionmentioning
confidence: 99%
“…The advisory system was deployed on an Android smartphone and incorporated text-to-speech support. A similar auditory solution was proposed in [47] but as an intelligent speed notification system, which repeatedly warned drivers against speeding. In [67], minibuses were proposed as alternatives to GSM for "transporting" data from smart meters to control centers.…”
mentioning
confidence: 99%
“…As a result, disaggregate analysis was limited to trips completed each taxi. The dataset used is availabe at [27].…”
Section: Experimental Designmentioning
confidence: 99%
“…Hull et al (2022b) showed that high-frequency mobility data on the order of one sample per second is needed for high-fidelity estimates of electric minibus taxi energy expenditure. Given the scarcity of such data, and the relative abundance of low-frequency mobility data that only captures one sample per minute (Ebot Eno Akpa et al, 2016), it would be invaluable to have simulation models that can simulate high-frequency mobility data from low-frequency data well enough to obtain high-fidelity estimates of energy expenditure. However, underlying assumptions in models and simulation setups may affect the output.…”
Section: Introductionmentioning
confidence: 99%